The economic burden of treatment failure amongst patients with irritable bowel syndrome with constipation or chronic constipation: a retrospective analysis of a Medicaid population. (August 2014) - Guerin, Annie; Carson, Robyn T.; Lewis, Barbara; Yin, Donald; Kaminsky, Michael; Wu, Eric
Abstract Objective: To compare healthcare resource utilization (HRU) and costs between patients with irritable bowel syndrome with constipation (IBS-C) or chronic constipation (CC) with and without evidence of treatment failure. Methods: Claims data from the Missouri Medicaid program were used to identify adults with IBS-C or CC treated for constipation. IBS-C patients were required to have ≥2 constipation therapy claims, and the index date was defined as the date of the first constipation therapy claim within 12 months after an IBS diagnosis. For CC, the index date was defined as the date of the first constipation treatment claim followed by a second claim for constipation treatment or diagnosis between 60 days and 12 months later. Indicators of treatment failure were: switch/addition of constipation therapy, IBS- or constipation-related inpatient/emergency admission, megacolon/fecal impaction, constipation-related surgery/procedure, or aggressive prescription treatments. Annual incremental HRU and costs (public payer perspective) were compared between patients with and without treatment failure. Incidence rate ratios (IRRs) and cost differences are reported. Results: In total, 2830 patients with IBS-C and 8745 with CC were selected. Approximately 50% of patients had ≥1 indicator of treatment failure. After adjusting for confounding factors, patients with treatment failure experienced higher HRU, particularly in inpatient days (IRR = 1.75 for IBS-C; IRR = 1.54 for CC) and higher total healthcare costs of 4353 in IBS-C patients and 2978 in CC patients. Medical service costs were the primary driver of the incremental costs associated with treatment failure, making up 71.3% and 67.0% of the total incremental healthcare costs of the IBS-C and CC samples, respectively. Limitations: Sample was limited to Medicaid patients in Missouri. Claims data were used to infer treatment failure. Conclusion: Treatment failure is frequent among IBS-C and CC patients, and sub-optimal treatment response with available IBS-C and CC therapies may lead to substantial HRU and healthcare costs.